Effects of reproductive stages on the prevalence of the normal flora in the doe - Ajaman, Norazmanita Edayu (2016)
The genital tract of animals is known to harbour non-specific bacteria known as ῝normal flora῝ but under certain circumstances they can be opportunistic pathogen. Generally, variety of bacteria have been isolated but their role and mechanism are not well understood. This study was designed to determine the prevalence of normal bacteria in the vaginal of pregnant and non-pregnant doe with the aims to isolate and identify those bacteria and relate with the different stages of reproduction. For this purpose, a number of fourteen sterile vaginal swabs were collected from 2 groups of doe; non pregnant and pregnant doe (n = 7). The swabs were cultured and incubated for 24h and morphology of the colonies were recorded. Subculture was done to obtain the pure colonies. Gram staining was performed followed by biochemical test accordingly. Bacteria isolated from the vagina of the pregnant group showed higher percentage (55.6%) than non-pregnant group (44.4%). The most dominant bacteria belong to the Stapylococci (58.33%) followed by Streptococci and Enterococcus (8.33%) and other species were isolated at relatively lower rates in both groups. This study showed that hormonal changes during different stages of reproduction had effect on the vaginal bacterial population.